Prevalence of Parasitic Contamination of Raw Vegetables in Sanandaj, Iran, in 2013 - ghasem zamini; peyman hamidi; Mohammad baqher bagher khadem erfan; Ashkan faridi; Esmaeil qhahramani; erfan babaei (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: Parasitic diseases have led to economic and health problems around the world. One of the most common ways for the transmission of these diseases is the consumption of raw vegetables contaminated with parasite. These diseases can be prevented through obtaining knowledge about the parasitic contamination of the vegetables. Regarding this, the aim of the present study was to evaluate the prevalence and type of raw vegetables  contamination in Sanandaj, Iran, in 2013.Methods: This cross-sectional study was conducted on 360 vegetable samples distributed in 60 greengroceries in Sanandaj in 2017. The data were analyzed using the SPSS version 16.Results: In total, 16.3% of the vegetable samples were contaminated with various types of parasites, including free-living nematode (12.2%), Entamoeba coli (1.7%), Giardia (0.8%), Blastocystis hominis (0.8%), and Dicrocoelium (0.8%). However, most of the contaminations (81.6%) were found in the vegetables, which were imported from regions other than Kurdistan province. Basil had the highest level of contamination, whereas coriander and lettuce had the lowest contamination level (P=0<05). Additionally, the vegetables had the highest and lowest contamination levels in the winter and spring, respectively.Conclusion: Regarding the findings of the present study, it is recommend to thoroughly perform parasite decontamination before the consumption of vegetables. Furthermore, the officials can prevent the parasitic diseases by  careful monitoring of public food distribution centers and controlling the source of vegetables in the winter.